Risk factors of contractor's corporate reputation - Ismail, Fuziah; Mustapa, Muzani; Mustapa, Fara Diva (2006)
Apparently, the quest for product and service differentiation has highlighted that intangible assets like reputation provide potential competitive advantage to an organisation. Reputation is built from ‘inside out’ of an organisation. The process would involved building a solid foundation of corporate vision and values that are strengthened by management policies, moulding one's image and responding to external expectations accordingly. Any action by an organisation has a direct impact on its reputation, which may damage it. Literature showed that the risk factors involved vary considerably. This paper therefore set out to establish the issues impacting corporate reputation of a construction company and prioritizes it.